Powder metallurgy product and preparation method and application thereof

By adding nickel-covered graphite, titanium powder, boron carbide and cerium oxide to the iron-based alloy, and forming a titanium boron system and TiC ceramic phase through laser cladding technology, the problem of hardness and toughness of iron-based alloy powder metallurgy products is solved, and better hardness and toughness effects are achieved.

CN119710675APending Publication Date: 2025-03-28YUYAO SHENGDA POWDER METALLURGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411659771.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

While the existing iron-based alloy powder metallurgy products increase hardness, their toughness is significantly reduced, resulting in prone to cracking during assembly.

Method used

These materials are present on the surface of powdered metallurgical products by adding nickel-covered graphite, titanium powder, boron carbide and cerium oxide to the iron-based alloy, and by laser cladding technology, to form a titanium boron system and TiC ceramic phase, and improve hardness and toughness.

Benefits of technology

It effectively improves the hardness and toughness of powder metallurgy products, reduces the risk of brittle fracture, and enhances the overall performance of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of functional iron-based alloy preparation, in particular to a powder metallurgy product and a preparation method and application thereof. The invention relates to a powder metallurgy product which comprises the following raw materials in parts by mass: 90 to 110 parts of AB powder-FD2080, 0.1 to 0.6 part of graphite, 0.4 to 0.6 part of micro powder wax and 0.2 to 0.4 part of manganese sulfide. The preparation method of the powder metallurgy product comprises the steps that firstly, AB powder-FD2080, graphite, micronized wax and manganese sulfide are mixed and subjected to extrusion forming, then the mixture is transferred into a sintering furnace, the temperature is increased to 1100-1200 DEG C, heat preservation is conducted for 20-40 min, then the temperature is slowly reduced to the room temperature, the cooling time is 2-4 h, and finally the powder metallurgy product is obtained. The powder metallurgy product has excellent hardness and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of functional iron-based alloys, and more specifically, to a powder metallurgy product and a preparation method and application thereof. Background Art

[0002] Powder metallurgy is a process technology that uses metal powder or a mixture of metal and non-metal powder as raw material to manufacture metal materials, composite materials and various types of products through processes such as pressing, molding and sintering. Its production process is similar to that of ceramic products, so it is also called metal ceramic method.

[0003] Powder metallurgy saves materials and energy and is suitable for mass production. In order to further improve the performance of powder metallurgy products, alloy elements are often added to iron powder to form prefabricated iron-based alloys, such as AB powder FD2080.

[0004] FD2080 contains trace amounts of carbon, copper, nickel and chromium, thus obtaining excellent mechanical strength and various physical properties.

[0005] However, in actual production, the hardness of the FD2080 product is slightly insufficient. In this regard, the applicant considered enhancing the hardness of the FD2080 product by adding graphite, micro-powder wax and manganese sulfide. However, at the same time, the brittleness of the FD2080 product is also significantly increased, so that cracks are easily caused during product assembly. Therefore, there is an urgent need for a powder metallurgy product with both excellent hardness and toughness. Summary of the invention

[0006] In order to improve the defect that conventional iron-based alloys have difficulty in achieving both hardness and toughness, the present application provides a powder metallurgy product and a preparation method and application thereof.

[0007] In a first aspect, the present application provides a powder metallurgy product, which adopts the following technical solution: A powder metallurgy product comprises the following raw materials in parts by weight: 90-110 parts of AB powder-FD2080, 0.1-0.6 parts of graphite, 0.4-0.6 parts of micro powder wax and 0.2-0.4 parts of manganese sulfide.

[0008] The reason for the increased brittleness of FD2080 products is that too much graphite is added. Excessive graphite can form a large number of graphite flakes or lumps in the iron matrix, thereby weakening the continuity of the entire powder metallurgy product. At the same time, due to the high brittleness of graphite, when the powder metallurgy product is subjected to stress, the powder metallurgy product is prone to brittle fracture along the graphite flakes or graphite lumps, thereby significantly reducing the toughness of the powder metallurgy product.

[0009] Preferably, the graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:(2-3).

[0010] The reason why graphite easily forms graphite flakes or graphite lumps is that graphite has low density and poor fluidity, and is not easy to be fully mixed with other powders. When graphite is added in the form of nickel-coated graphite, the fluidity of the graphite will be significantly increased, thereby increasing the amount of graphite added.

[0011] Moreover, nickel can form a solid solution in the iron matrix, thereby improving the strength and hardness of powder metallurgy products. At the same time, since nickel can reduce the brittle transition temperature of the material, the addition of nickel can significantly improve the toughness of powder metallurgy products at low temperatures and reduce the risk of brittle fracture.

[0012] Preferably, the powder metallurgy product further comprises titanium powder, and the titanium powder and nickel-coated graphite are present on the surface of the powder metallurgy product through laser cladding.

[0013] Although the use of nickel-coated graphite can effectively improve the hardness and toughness of powder metallurgy products, the improvement in hardness is still insufficient. After the addition of titanium powder, the surface of the powder metallurgy product will grow in situ to form a TiC ceramic phase, and the TiC ceramic phase gradually changes from granular to petal-shaped, and then to dendrite-shaped during the laser cladding process, thereby obtaining better hardness and toughness.

[0014] Preferably, the powder metallurgy product further includes boron carbide, and titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding.

[0015] When titanium powder, nickel-coated graphite and boron carbide are used together, a titanium boron system will be formed between the titanium powder and the boron carbide. Titanium boron has the characteristics of high modulus and high hardness, and also has high temperature resistance, oxidation resistance and excellent wear resistance. Therefore, the formation of the titanium boron system can further improve the hardness of powder metallurgy products.

[0016] However, similar to graphite, titanium boron itself is also relatively brittle, which leads to a significant reduction in the toughness of powder metallurgy products. However, when titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding, the titanium boron particles will be generated in situ, so their size will be smaller, the eutectic particles will be more perfect, and the extra titanium carbide will be attached to the titanium boron and be spherical or petal-shaped, thereby promoting the hardness of the powder metallurgy product while improving its toughness.

[0017] Preferably, the powder metallurgy product further comprises cerium oxide, and titanium powder, nickel-coated graphite, boron carbide and cerium oxide are present on the surface of the powder metallurgy product by laser cladding.

[0018] The addition of cerium oxide can reduce the porosity of the laser cladding layer, refine the grain size, form a denser and more stable passivation film, improve the organizational uniformity of the cladding layer, and reduce crack sensitivity, thereby enabling powder metallurgy products to obtain better hardness and toughness.

[0019] Preferably, the raw materials include the following parts by mass: 90-110 parts of AB powder-FD2080, 0.1-0.6 parts of graphite, 0.4-0.6 parts of micro powder wax, 0.2-0.4 parts of manganese sulfide, 0.6-1.0 parts of titanium powder, 0.2-0.4 parts of boron carbide and 0.4-0.6 parts of cerium oxide, wherein the graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10: (2-3).

[0020] In a second aspect, the present application provides a method for preparing a powder metallurgy product, using the following technical solution: A preparation method for a powder metallurgy product, the preparation method comprising: firstly mixing AB powder-FD2080, graphite, micro powder wax and manganese sulfide and extruding them, then transferring them to a sintering furnace, raising the temperature to 1100-1200°C, keeping the temperature for 20-40 minutes, and then slowly cooling to room temperature for 2-4 hours, and finally obtaining a powder metallurgy product.

[0021] A method for preparing a powder metallurgy product comprises the following steps: S1. First, AB powder-FD2080, micro powder wax and manganese sulfide are mixed and extruded, and then transferred to a sintering furnace, the temperature is raised to 1100-1200°C, kept warm for 20-40 minutes, and then slowly cooled to room temperature for 2-4 hours to finally obtain a powder metallurgy base material; S2. Mix nickel-coated graphite, titanium powder, boron carbide and cerium oxide, and then lay the mixture on the surface of the powder metallurgy base material, and then perform laser cladding by a YAG fixed laser. The laser cladding parameters are as follows: Scanning speed 180mm / min, current 200A, defocus 0mm, pulse width 6ms, frequency 8Hz, overlap rate 50%, argon protection, argon flow rate 12L / min; After laser cladding is completed, it is cooled to room temperature and finally cut.

[0022] In a third aspect, the present application provides an application of a powder metallurgy product, using the following technical solution: An application of a powder metallurgy product, wherein the powder metallurgy product is used for preparing face gears or iron bars.

[0023] In summary, this application has the following beneficial effects: 1. The reason why graphite easily forms graphite flakes or graphite agglomerates is that graphite has low density and poor fluidity, and is not easy to fully mix with other powders. When graphite is added in the form of nickel-coated graphite, the fluidity of graphite will be significantly increased, thereby increasing the amount of graphite added; Moreover, nickel can form a solid solution in the iron matrix, thereby improving the strength and hardness of powder metallurgy products. At the same time, since nickel can reduce the brittle transition temperature of the material, the addition of nickel can significantly improve the toughness of powder metallurgy products at low temperatures and reduce the risk of brittle fracture.

[0024] 2. Although the use of nickel-coated graphite can effectively improve the hardness and toughness of powder metallurgy products, the degree of hardness improvement is still insufficient. After the addition of titanium powder, the surface of the powder metallurgy product will grow in situ to form a TiC ceramic phase. During the laser cladding process, the TiC ceramic phase gradually changes from granular to petal-shaped and then to dendrite-shaped, thereby obtaining better hardness and toughness.

[0025] 3. When titanium powder, nickel-coated graphite and boron carbide are used together, a titanium boron system will be formed between titanium powder and boron carbide. Titanium boron has the characteristics of high modulus and high hardness, and also has high temperature resistance, oxidation resistance and excellent wear resistance. Therefore, the formation of the titanium boron system can further improve the hardness of powder metallurgy products; However, similar to graphite, titanium boron itself is also relatively brittle, which leads to a significant reduction in the toughness of powder metallurgy products. However, when titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding, the titanium boron particles will be generated in situ, so their size will be smaller, the eutectic particles will be more perfect, and the extra titanium carbide will be attached to the titanium boron and be spherical or petal-shaped, thereby promoting the hardness of the powder metallurgy product while improving its toughness.

[0026] 4. The addition of cerium oxide can reduce the porosity of the laser cladding layer, refine the grain size, form a denser and more stable passivation film, improve the organizational uniformity of the cladding layer, and reduce crack sensitivity, thereby enabling powder metallurgy products to obtain better hardness and toughness. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with Examples 1-10.

[0028] raw material AB powder-FD2080 Shandong Luyin New Materials; graphite CAS: 7782-42-5; micro powder wax BYK-981; Manganese sulfide CAS: 18820-29-6; Nickel CAS: 7440-02-0; Titanium CAS: 7440-32-6; Boron carbide CAS: 12069-32-8; Cerium oxide CAS: 1306-38-3.

[0029] Example Example 1 A powder metallurgy product comprises the following raw materials: 100g AB powder-FD2080, 0.1g graphite, 0.5g micro powder wax and 0.3g manganese sulfide.

[0030] The preparation method of powder metallurgy products is as follows: first, AB powder-FD2080, graphite, micro-powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to finally obtain a powder metallurgy product.

[0031] Example 2 A powder metallurgy product comprises the following raw materials: 100g AB powder-FD2080, 0.3g graphite, 0.5g micro powder wax and 0.3g manganese sulfide.

[0032] The preparation method of powder metallurgy products is as follows: first, AB powder-FD2080, graphite, micro-powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to finally obtain a powder metallurgy product.

[0033] Example 3 A powder metallurgy product comprises the following raw materials: 100g AB powder-FD2080, 0.6g graphite, 0.5g micro powder wax and 0.3g manganese sulfide.

[0034] The preparation method of powder metallurgy products is as follows: first, AB powder-FD2080, graphite, micro-powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to finally obtain a powder metallurgy product.

[0035] Example 4 The difference from Example 2 is that the graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:2.5; The preparation method of nickel-coated graphite is as follows: firstly, nickel is heated to a molten state, then graphite is added, mixed and stirred evenly, and finally cooled to room temperature, crushed and ground to 800 meshes to obtain nickel-coated graphite.

[0036] Example 5 The difference from Example 4 is that the powder metallurgy product includes the following raw materials: 100g AB powder-FD2080, 0.3g graphite, 0.5g micro-powder wax, 0.3g manganese sulfide and 0.8g titanium powder, and the graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:2.5.

[0037] The preparation method of powder metallurgy products is as follows: first, AB powder-FD2080, nickel-coated graphite, micro-powder wax, manganese sulfide and titanium powder are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly dropped to room temperature for 3 hours to finally obtain a powder metallurgy product.

[0038] Example 6 The difference from Example 4 is that the powder metallurgy product includes the following raw materials: 100g AB powder-FD2080, 0.3g graphite, 0.5g micro-powder wax, 0.3g manganese sulfide, 0.8g titanium powder and 0.3g boron carbide, and the graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:2.5.

[0039] The preparation method of powder metallurgy products is as follows: first, AB powder-FD2080, nickel-coated graphite, micro-powder wax, manganese sulfide, titanium powder and boron carbide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to finally obtain a powder metallurgy product.

[0040] Example 7 The difference from Example 6 is that titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding.

[0041] The method for preparing a powder metallurgy product comprises the following steps: S1. First, AB powder-FD2080, micro powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to obtain a powder metallurgy base material; S2. Mix nickel-coated graphite, titanium powder and boron carbide, and then lay the mixture on the surface of the powder metallurgy base material, and then perform laser cladding by a YAG fixed laser. The laser cladding parameters are as follows: Scanning speed 180mm / min, current 200A, defocus 0mm, pulse width 6ms, frequency 8Hz, overlap rate 50%, argon protection, argon flow rate 12L / min; After laser cladding is completed, it is cooled to room temperature and finally cut.

[0042] Example 8 The difference from Example 7 is that the powder metallurgy product includes the following masses of raw materials: 100 g AB powder-FD2080, 0.3 g graphite, 0.5 g micro-powder wax, 0.3 g manganese sulfide, 0.8 g titanium powder, 0.3 g boron carbide and 0.5 g cerium oxide, the graphite is added in the form of nickel-coated graphite, the mass ratio of nickel to graphite is 10:2.5, and the titanium powder, nickel-coated graphite, boron carbide and cerium oxide are present on the surface of the powder metallurgy product by laser cladding.

[0043] The method for preparing a powder metallurgy product comprises the following steps: S1. First, AB powder-FD2080, micro powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1120°C, kept warm for 30 minutes, and then slowly cooled to room temperature for 3 hours to obtain a powder metallurgy base material; S2. Mix nickel-coated graphite, titanium powder, boron carbide and cerium oxide, and then lay the mixture on the surface of the powder metallurgy base material, and then perform laser cladding by a YAG fixed laser. The laser cladding parameters are as follows: Scanning speed 180mm / min, current 200A, defocus 0mm, pulse width 6ms, frequency 8Hz, overlap rate 50%, argon protection, argon flow rate 12L / min; After laser cladding is completed, it is cooled to room temperature and finally cut.

[0044] Examples 9-10 The difference from Example 8 is that the addition amounts of the components of the powder metallurgy product are different, as shown in Table 1.

[0045] Table 1 Addition amount of each component of the powder metallurgy product in Examples 8-10 / g Example 8 Example 9 Example 10 AB powder 100 110 90 graphite 0.3 0.6 0.1 Micronized wax 0.5 0.4 0.6 Manganese sulfide 0.3 0.2 0.4 Titanium powder 0.8 0.6 1.0 Boron Carbide 0.3 0.4 0.2 Cerium Oxide 0.5 0.6 0.4 Performance testing Detection Methods 1. Hardness test Three samples were taken from Examples 1-10 respectively, and then the Rockwell hardness of the samples was tested with reference to GB / T230.1-2018 "Rockwell hardness test for metallic materials - Part 1: Test method" and the average value was taken.

[0046] 2. Breaking Strength Test Three samples were taken from Examples 1-10 respectively, and then the fracture strength of the samples was tested with reference to GB228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method" and the average value was taken.

[0047] The test data are shown in Table 2.

[0048] Table 2 Test data table of Examples 1-10 Rockwell hardness Breaking strength / MPa Example 1 51 761 Example 2 54 707 Example 3 60 613 Example 4 56 766 Example 5 59 793 Example 6 62 811 Example 7 64 843 Example 8 66 869 Example 9 63 839 Example 10 62 841 Referring to Examples 1-3 and in combination with Table 2, it can be seen that among Examples 1-3, Example 1 has a better and more excellent fracture strength, but the Rockwell hardness of Example 1 is the worst, Example 3 has a better Rockwell hardness, but the fracture strength of Example 3 is the worst, and the Rockwell hardness and fracture strength of Example 2 are more balanced.

[0049] This shows that with the increase of graphite addition, the Rockwell hardness of powder metallurgy products will gradually increase. However, at the same time, the fracture strength of powder metallurgy products will gradually deteriorate. The reason is that a small amount of graphite can serve as the nucleus for grain growth and promote grain refinement. At the same time, graphite can also form a composite phase with trace elements in FD2080, thereby significantly enhancing the Rockwell hardness of powder metallurgy products.

[0050] However, too much graphite can form a large number of graphite flakes or lumps in the iron matrix, thereby weakening the continuity of the entire powder metallurgy product. At the same time, due to the high brittleness of graphite, when the powder metallurgy product is subjected to stress, the powder metallurgy product is prone to brittle fracture along the graphite flakes or graphite lumps, thereby significantly reducing the toughness of the powder metallurgy product.

[0051] In summary, the addition amount of graphite is relatively better when it is 0.3g.

[0052] Referring to Example 2 and Example 4 and combining with Table 2, it can be seen that compared with Example 2, the Rockwell hardness and fracture strength of Example 4 are significantly improved, which shows that the form of nickel-coated graphite can further improve the hardness and toughness of powder metallurgy products.

[0053] The reason is that graphite easily forms graphite flakes or graphite lumps because graphite has low density and poor fluidity, and is not easy to fully mix with other powders. When graphite is added in the form of nickel-coated graphite, the fluidity of the graphite will increase significantly, thereby increasing the amount of graphite added.

[0054] Moreover, nickel can form a solid solution in the iron matrix, thereby improving the strength and hardness of powder metallurgy products. At the same time, since nickel can reduce the brittle transition temperature of the material, the addition of nickel can significantly improve the toughness of powder metallurgy products at low temperatures and reduce the risk of brittle fracture.

[0055] Referring to Example 4 and Example 5 and combining with Table 2, it can be seen that compared with Example 4, the Rockwell hardness and fracture strength of Example 5 are slightly improved, which shows that the addition of titanium powder can improve the hardness and toughness of powder metallurgy products to a certain extent.

[0056] The reason is that although the use of nickel-coated graphite can effectively improve the hardness and toughness of powder metallurgy products, the hardness improvement is still insufficient. After the addition of titanium powder, the surface of the powder metallurgy product will grow in situ to form a TiC ceramic phase, and the TiC ceramic phase gradually changes from granular to petal-shaped and then to dendrite-shaped during the laser cladding process, thereby obtaining better hardness and toughness.

[0057] Referring to Example 5 and Example 6 and combining with Table 2, it can be seen that compared with Example 5, the Rockwell hardness and fracture strength of Example 6 are slightly improved, which shows that the addition of boron carbide can improve the hardness and toughness of powder metallurgy products to a certain extent.

[0058] The reason is that when titanium powder, nickel-coated graphite and boron carbide are used together, a titanium boron system will be formed between the titanium powder and the boron carbide. Titanium boron has the characteristics of high modulus and high hardness, and also has high temperature resistance, oxidation resistance and excellent wear resistance. Therefore, the formation of the titanium boron system can further improve the hardness and toughness of powder metallurgy products.

[0059] Referring to Example 6 and Example 7 and combining with Table 2, it can be seen that compared with Example 6, the Rockwell hardness and fracture strength of Example 7 are significantly improved, which shows that the titanium powder, nickel-coated graphite and boron carbide present on the surface of the powder metallurgy product through laser cladding can further improve the hardness and toughness of the powder metallurgy product.

[0060] The reason is that although the formation of titanium boron system can further improve the hardness and toughness of powder metallurgy products, similar to graphite, titanium boron itself is also relatively brittle, which leads to a significant decrease in the toughness of powder metallurgy products.

[0061] However, when titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding, since the titanium boron particles will be generated in situ, their size will be relatively smaller and the eutectic particles will be more perfect. The additionally generated titanium carbide will adhere to the titanium boron and be spherical or petal-shaped, thereby promoting the hardness and toughness of the powder metallurgy product to be improved.

[0062] Referring to Example 7 and Example 8 and combining with Table 2, it can be seen that compared with Example 7, the Rockwell hardness and fracture strength of Example 8 are significantly improved, which shows that the addition of cerium oxide can further improve the hardness and toughness of powder metallurgy products.

[0063] The reason is that the addition of cerium oxide can reduce the porosity of the laser cladding layer, refine the grain size, form a denser and more stable passivation film, improve the organizational uniformity of the cladding layer, and reduce crack sensitivity, thereby enabling powder metallurgy products to obtain better hardness and toughness.

[0064] Referring to Examples 8-10 and in combination with Table 2, it can be seen that, relative to Example 8, the Rockwell hardness and fracture toughness of Examples 9-10 are significantly reduced, which indicates that when the components of the powder metallurgy product are added in the amounts of Example 8, the prepared powder metallurgy product will have better hardness and toughness.

[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A powder metallurgy product, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of AB powder-FD2080, 0.1-0.6 parts of graphite, 0.4-0.6 parts of micro powder wax and 0.2-0.4 parts of manganese sulfide.

2. The powder metallurgy product according to claim 1, characterized in that: The graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:(2-3).

3. The powder metallurgy product according to claim 2, characterized in that: The powder metallurgy product also includes titanium powder, and the titanium powder and nickel-coated graphite are present on the surface of the powder metallurgy product through laser cladding.

4. The powder metallurgy product according to claim 3, characterized in that: The powder metallurgy product also includes boron carbide, and titanium powder, nickel-coated graphite and boron carbide are present on the surface of the powder metallurgy product through laser cladding.

5. The powder metallurgy product according to claim 4, characterized in that: The powder metallurgy product also includes cerium oxide, and titanium powder, nickel-coated graphite, boron carbide and cerium oxide are present on the surface of the powder metallurgy product through laser cladding.

6. The powder metallurgy product according to claim 5, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of AB powder-FD2080, 0.1-0.6 parts of graphite, 0.4-0.6 parts of micro powder wax, 0.2-0.4 parts of manganese sulfide, 0.6-1.0 parts of titanium powder, 0.2-0.4 parts of boron carbide and 0.4-0.6 parts of cerium oxide. The graphite is added in the form of nickel-coated graphite, and the mass ratio of nickel to graphite is 10:(2-3).

7. A method for preparing a powder metallurgy product according to any one of claims 1 to 6, characterized in that: The preparation method is as follows: firstly, AB powder-FD2080, graphite, micro powder wax and manganese sulfide are mixed and extruded, then transferred to a sintering furnace, the temperature is raised to 1100-1200°C, kept warm for 20-40 minutes, and then slowly cooled to room temperature for 2-4 hours to finally obtain a powder metallurgy product.

8. A method for preparing a powder metallurgy product according to any one of claims 5 to 6, characterized in that: The following steps are involved: S1. First, AB powder-FD2080, micro powder wax and manganese sulfide are mixed and extruded, and then transferred to a sintering furnace, the temperature is raised to 1100-1200°C, kept warm for 20-40 minutes, and then slowly cooled to room temperature for 2-4 hours to finally obtain a powder metallurgy base material; S2. Mix nickel-coated graphite, titanium powder, boron carbide and cerium oxide, and then lay the mixture on the surface of the powder metallurgy base material, and then perform laser cladding by a YAG fixed laser. The laser cladding parameters are as follows: Scanning speed 180mm / min, current 200A, defocus 0mm, pulse width 6ms, frequency 8Hz, overlap rate 50%, argon protection, argon flow rate 12L / min; After laser cladding is completed, it is cooled to room temperature and finally cut.

9. An application of the powder metallurgy product according to any one of claims 1 to 6, characterized in that: The powder metallurgy product is used for preparing face gears or iron bars.